Antibacterial efficiency of magnetron sputtered TiO2 on poly(methyl methacrylate) - Nuñez, Julius Andrew P. (Animo Repository, 2017)
Titanium dioxide (TiO2) particles were deposited on poly(methyl methacrylate) (PMMA) by magnetron sputtering of Ti at varying O2/Ar flow rate ratio and at varying discharge current using a Compact Planar Magnetron (CPM) sputtering device. The deposited TiO2 on PMMA samples were characterized using X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). The samples were tested for their photoinduced hydrophilicity, and antibacterial activity against Escherichia coli (E.coli). XPS, FTIR and EDX analyses confirmed the presence of TiO2 on the surface of PMMA. XPS spectra revealed the presence of Ti 2p and O 1 s bands on the surface of the samples and the EDX spectra showed that the elemental ratio of Ti and O ranged from 26 to 30% and 69 to 73%, respectively. SEM showed that the deposited TiO2 was relatively smooth with micro islands of titanium at the surface. Photoinduced hydrophilicity was observed for all samples after 10 min of UV irradiation; this was seen from the reduction of the water contact angles on the UV irradiated samples from 66° to as low as